The Requirements of Using E-Learning as Viewed by the Faculty Members at the University of Tripoli, Faculty of Education Tripoli as a model. (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:This study aims to explore the requirements for the use of e-learning in university teaching from the point of view of faculty members at the Faculty of Education Tripoli. The descriptive analytical method was to achieve the research objectives and understand the research problem. Questionnaires were distributed to 79 of the teacher-educators of the Faculty of Education Tripoli who were chosen randomly. Data were analyzed using the Statistical Package for Social Sciences known as (SPSS). Results revealed the importance of material requirements (physical environment), including the Internet, computers, and their accessories. Results also emphasized the need for all faculty members to have computers and Internet skills and to employ them in the educational process effectively. In addition, the results showed that the prevailing point of view among the teacher-educators is to distribute and test the course after verifying its validity and to develop the skill of independent learning, which indicates their significance as perceived by the respondents.